Radiotherapy-induced ferroptosis for cancer treatment - Beretta, Giovanni L.; Zaffaroni, Nadia (Frontiers in Molecular Biosciences, 2023)
Ferroptosis is a regulated cell death mechanism controlled by iron, amino acid and reactive oxygen species metabolisms, which is very relevant for cancer therapy. Radiotherapy-induced ferroptosis is critical for tumor suppression and several preclinical studies have demonstrated that the combination of ionizing radiation with small molecules or nano-systems is effective in combating cancer growth and overcoming drug or ionizing radiation resistance. Here, we briefly overview the mechanisms of ferroptosis and the cross-talk existing between the cellular pathways activated by ferroptosis and those induced by radiotherapy. Lastly, we discuss the recently reported combinational studies involving radiotherapy, small molecules as well as nano-systems and report the recent findings achieved in this field for the treatment of tumors.